2D-WS2‑Coated Architectural Modified Cellulose Paper-Based Photosensitive Triboelectric Nanogenerators - Sumit Chahal (10668163) (2025)
The growing demand for sustainable and multifunctional energy harvesting systems has propelled the advancement of hybrid energy harvesting systems. Here, we report a sustainable triboelectric nanogenerator architecture based on cellulose paper coated with two-dimensional (2D) tungsten disulfide (WS2) nanosheets for simultaneous mechanical and light-assisted energy harvesting. The WS2 nanosheets were synthesized by a simple liquid-phase exfoliation method and uniformly deposited on cellulose paper. Three modified device geometries, hinge, zigzag, and elliptical, were fabricated using WS2-coated paper as the tribopositive layer and Kapton as the tribonegative counterpart. The elliptical design showed the best hybrid performance, generating 170.2 V under combined finger tapping and near-infrared (730 nm) illumination, significantly higher than 150.5 V under visible light and 97.9 V in the dark. The device also achieved a peak power density of ∼98 mW m–2. Furthermore, the WS2-coated paper exhibited broadband photodetection with rise/decay times of ∼2.86/2.87 s under visible light exposure and ∼1.92/1.90 s under near-infrared light exposure. This higher output under NIR light is attributed to the synergistic effects of the photothermal and photogeneration mechanisms in the WS2 material. This work demonstrates a low-cost and scalable strategy for flexible nanogenerators that integrate mechanical and optical energy harvesting, paving the way for self-powered wearable electronics and optoelectronic devices.